Inhibition of the Autophagy Pathway Synergistically Potentiates the Cytotoxic Activity of Givinostat (ITF2357) on Human Glioblastoma Cancer Stem Cells - Angeletti, Francesca; Fossati, Gianluca; Pattarozzi, Alessandra; Würth, Roberto; Solari, Agnese; Daga, Antonio; Masiello, Irene; Barbieri, Federica; Florio, Tullio; Comincini, Sergio (Frontiers in Molecular Neuroscience, 2016)
Increasing evidence highlighted the role of cancer stem cells (CSCs) in the development of tumor resistance to therapy, particularly in glioblastoma (GBM). Therefore, the development of new therapies, specifically directed against GBM CSCs, constitutes an important research avenue. Considering the extended range of cancer-related pathways modulated by histone acetylation/deacetylation processes, we studied the anti-proliferative and pro-apoptotic efficacy of givinostat (GVS), a pan-histone deacetylase inhibitor, on cell cultures enriched in CSCs, isolated from nine human GBMs. We report that GVS induced a significant reduction of viability and self-renewal ability in all GBM CSC cultures; conversely, GVS exposure did not cause a significant cytotoxic activity toward differentiated GBM cells and normal mesenchymal human stem cells. Analysing the cellular and molecular mechanisms involved, we demonstrated that GVS affected CSC viability through the activation of programmed cell death pathways. In particular, a marked stimulation of macroautophagy was observed after GVS treatment. To understand the functional link between GVS treatment and autophagy activation, different genetic and pharmacological interfering strategies were used. We show that the up-regulation of the autophagy process, obtained by deprivation of growth factors, induced a reduction of CSC sensitivity to GVS, while the pharmacological inhibition of the autophagy pathway and the silencing of the key autophagy gene ATG7, increased the cell death rate induced by GVS. Altogether these findings suggest that autophagy represents a pro-survival mechanism activated by GBM CSCs to counteract the efficacy of the anti-proliferative activity of GVS. In conclusion, we demonstrate that GVS is a novel pharmacological tool able to target GBM CSC viability and its efficacy can be enhanced by autophagy inhibitory strategies.